1992
DOI: 10.1080/01952307.1992.11761521
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use and Abuse in an Urban Veteran Spinal Cord Injured Population

Abstract: Substance abuse in the spinal cord injured (SCI) population has been addressed in a few controlled studies. These reports have led to the belief that many SCI patients were illicit drug users prior to their injury and that their drug abuse was a contributing cause of their accidents. One large study determined from answers obtained on a questionnaire that drug abuse, other than alcohol, was prevalent among injured veterans. Our study uses urine toxicology to determine the frequency of drug use and abuse, exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…26 The results of this study are also consistent with other studies assessing alcohol problems among consecutive inpatients with SCI. 1,3,16,17 Interestingly, rates of significant alcohol problems based on self-reports of consecutive inpatients appear much higher than estimates based on community surveys. Young et al 4 surveyed 123 community residents with SCI and found that 21% of respondents reported significant alcohol-related problems based on their SMAST scores.…”
Section: Alcohol Usementioning
confidence: 79%
See 1 more Smart Citation
“…26 The results of this study are also consistent with other studies assessing alcohol problems among consecutive inpatients with SCI. 1,3,16,17 Interestingly, rates of significant alcohol problems based on self-reports of consecutive inpatients appear much higher than estimates based on community surveys. Young et al 4 surveyed 123 community residents with SCI and found that 21% of respondents reported significant alcohol-related problems based on their SMAST scores.…”
Section: Alcohol Usementioning
confidence: 79%
“…Several studies of preinjury alcohol and drug use have reported data based on admission toxicology screens or serum alcohol levels, with positive blood alcohol levels (BALs) ranging from 40 to 44% and positive drug toxicology screens ranging from 27 to 35%. 1,3,16,17 However, many estimates of drug use based on toxicology screens may have limited validity because they screen for presence of opiates or benzodiazepines. These drugs are often administered in emergency medical treatment and may represent a possible confound.…”
mentioning
confidence: 99%
“…En general, hay una amplia variedad de metodologías y variables medidas entre estudios. Gran parte de la literatura se centraba en la medición de ingesta de alcohol o de alcoholemias (Furlan y Fehlings, 2013;McKinley et al, 1999;Rothstein, Levy, Fecher, Gordon, y Bauman, 1992;Stroud et al, 2011;Turner et al, 2003). Varios estudios evaluaron tabaco y otras sustancias legales (p.…”
Section: Discussionunclassified
“…Rothstein et al 11 examined the frequency of drug use and abuse in over 150 patients from a Veterans Affairs Medical Center in the US. Urinary concentrations of various drugs were determined in a blinded fashion, with the investigators finding that the use of nonprescribed drugs was surprisingly low.…”
Section: Discussionmentioning
confidence: 99%